Life’s organization between matter and form: Neo-Aristotelian approaches and biosemiotics - Karaca, Çağlar (Springer Science and Business Media LLC, 2021)
In this paper, I discuss the neo-Aristotelian approaches, which usually reinterpret Aristotle's ideas on form and/or borrow the notion of formal cause without engaging with the broader implications of Aristotle's metaphysics. In opposition to these approaches, I claim that biosemiotics can propose an alternative view on life's form. Specifically, I examine the proposals to replace the formal cause with gene-centrism, functionalism, and structuralism. After critically addressing these approaches, I discuss the problems of reconciling Aristotelianism with the modern view of life's organization. I claim that the notion of the final cause proposes a cosmological hierarchy and that this is the main problem with applying the formal cause to biology. An alternative categorization of conceptualizing life's form involves (1) the processual identity, (2) relational property clusters, and (3) context-dependent transmission of representational units. The third category points to a semiotic basis of the form of life. In this context, I offer to readjust the focus of the problem of matter-form duality by pointing out that form is primarily an issue of the subject-object relation. Biosemiotics helps to understand the constructive role of symbolic representation in living systems, which is crucial to extend the analysis of the form from cognitive representations to external phenomena. Emergence of subjectivity and perspectivity of interactions are key elements to bridge the form and actual processes within a non-hylomorphic account. To demonstrate transitions from the physical influence of shapes to the organic recognition of forms, I address the biological studies on the synchronization of coincidental inputs and enzyme specificity.
Keywords: Philosophy; Life; Terminology as Topic; Selection, Genetic; Biology; 11. Sustainability; 7. Clean energy